La radio ‘an tan Wobè’. Le Nègre et l’Amiral de Raphaël Confiant - Paraboschi, Francesca (Ponti/Ponts, 2021)
This essay is based on the novel Le Nègre et l’Amiral by Raphaël Confiant. It takes into consideration the role of the radio as a media during the Second World War in Martinique and the part played by the propaganda. The analysis focuses on the characters’ urge to listen to the news, despite the prohibition to listen to the forbidden broadcasting stations, also despite the difficulties in tuning in the right wavelength and in understanding the radio speech (in French and in English). The analyses shows how the characters’ patriotism is due to a cultural enslavement, giving rise to an extraordinary confusion in their political ideas. On one hand the value of the white speech is questioned, often providing contradictions and incomprehensibility, on the other hand the black speech is praised, for revealing itself more authentic and beautifully inventive. The written word form of the novel writing is eventually approached to point out the difficult and remarkable work of the writer, combining the oral creole speech in a literary text.